2005
DOI: 10.1007/s10164-005-0169-z
|View full text |Cite
|
Sign up to set email alerts
|

Use of a magnetic compass for Y-axis orientation in premetamorphic newts (Triturus boscai)

Abstract: Experiments were carried out to investigate whether premetamorphic larvae of Bosca's newt (Triturus boscai) are capable of using the geomagnetic field for Y-axis orientation (i.e., orientation toward and away from shore). Larvae were trained outdoor in two different training configurations, using one training tank aligned along the magnetic north-south axis, with shore facing north, and another training tank positioned with its length along the east-west axis, with shore located west. After training, premetamo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 29 publications
(41 reference statements)
1
9
0
Order By: Relevance
“…Bimodal y‐axis magnetic compass orientation has also been observed in amphibian urodeles (eastern red‐spotted newts, N. viridescens : Deutschlander et al. 2000; Bosca's newts, L. boscai : Rodríguez‐García & Diego‐Rasilla 2006) and anurans (bullfrogs, R. catesbeiana : Freake et al. 2002; Freake & Phillips 2005), and it has been suggested that variation in training/testing protocol, and in individual animal motivation, may produce either unimodal or bimodal orientation relative to the y‐axis (Freake et al.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Bimodal y‐axis magnetic compass orientation has also been observed in amphibian urodeles (eastern red‐spotted newts, N. viridescens : Deutschlander et al. 2000; Bosca's newts, L. boscai : Rodríguez‐García & Diego‐Rasilla 2006) and anurans (bullfrogs, R. catesbeiana : Freake et al. 2002; Freake & Phillips 2005), and it has been suggested that variation in training/testing protocol, and in individual animal motivation, may produce either unimodal or bimodal orientation relative to the y‐axis (Freake et al.…”
Section: Discussionmentioning
confidence: 99%
“…2002; Diego‐Rasilla et al. 2005; Freake & Phillips 2005; Rodríguez‐García & Diego‐Rasilla 2006) indicate that sensitivity to the alignment of the magnetic field is a widespread sensory capability not only among urodele, but also among anuran, amphibians.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, evidence for y-axis magnetic compass orientation among adult amphibians has only been reported in Eastern red-spotted newts, Notophthalmus viridescens (Phillips, 1986a,b), while among larval amphibians it has been reported for three species of frogs (Lithobates catesbeianus, Pelophylax perezi and Rana temporaria (Diego-Rasilla et al, 2013;Diego-Rasilla and Phillips, 2007;Freake et al, 2002), and one species of urodele, Lissotriton boscai (Rodríguez-García and Diego-Rasilla, 2006).…”
Section: Introductionmentioning
confidence: 97%